Silencing of long noncoding INHBA antisense RNA1 suppresses proliferation, migration, and extracellular matrix deposition in human hypertrophic scar fibroblasts via regulating microRNA-141-3p/myeloid cell leukemia 1 axis. Issue 1 (1st January 2021) - Yang, Yan; Xiao, Chun; Liu, Kang; Song, Liping; Zhang, Yonggang; Dong, Birong
ABSTRACT: Long noncoding RNAs (lncRNAs) play vital roles in the progression of hypertrophic scar (HS). We aimed to explore the effect of lncRNA INHBA Antisense RNA1 (INHBA-AS1) in the formation of HS and identify the potential mechanisms. INHBA-AS1 and microRNA (miR)-141-3p expression in human HS fibroblasts (hHSFs) was determined using RT-qPCR. LncBase online database predicted that miR-141-3p could be a putative target of INHBA-AS1, and the interaction of them was verified by luciferase reporter assay and RNA immunoprecipitation (RIP) assay. Subsequently, following INHBA-AS1 silencing, cell proliferation and migration were evaluated using CCK-8, wound healing and Transwell assays. And rescue experiments were conducted to analyze the impact of INHBA-AS1 and miR-141-3p on HS formation. Immunofluorescence assay was employed to examine the expression of extracellular matrix (ECM)-related proteins. Then, StarBase database predicated that myeloid cell leukemia 1 (MCL1) was a potential target of miR-141-3p, which was verified with luciferase reporter- and RIP assays. Finally, cell function and ECM deposition were determined after MCL1-downregulation. INHBA-AS1 was significantly elevated while miR-141-3p was notably reduced in hHSFs. And it was confirmed that miR-141-3p was directly targeted by INHBA-AS1. Moreover, INHBA-AS1 silencing markedly attenuated the proliferation, migration and ECM accumulation of hHSFs, which were restored after miR-141-3p silencing. Additionally, MCL1 was confirmed as a direct target of miR-141-3p, and MCL1-knockdown remarkably alleviated the proliferation, migration and ECM accumulation of hHSFs. INHBA-AS1-knockdown suppresses the formation of HS by regulating miR-141-3p/MCL1 pathway, suggesting a promising therapeutic target for HS treatment. Graphical Abstract: uf0001